Analisis Pengendalian Kualitas Produk dengan Metode Statistical Process Control Pada PT Glory Industrial di Sragen - Yernia Aloensia Putri; Sunarso Sunarso; Erni Widajanti (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The aim of this research is to analyze the production quality control policy at PT Glory Industrial in Sragen, to identify the factors that cause damage and loss to products produced by PT Glory Industrial in Sragen. This research is included in the type of case study research at PT Glory Industrial in Sragen by conducting a survey to the company. This research only covers production quality control at PT Glory Industrial in Sragen. Product quality control uses the Statistical Process Control method. Starting with determining quality standards then production results, then damaged production is analyzed through quality control using Statistical Process Control, so that you can receive analysis results that can be useful for PT Glory Industrial in Sragen. The results of the research show that the implementation of product quality control at PT Glory Industrial has not been under control, this is proven by the production process that there were 4 points that exceeded the upper control limit (UCL) and lower control limit (LCL). Occurred on the months February (0,023), June (0,084), September (0,022) and November (0,075). From this data, it can be seen that there are still those who exceed the control limits, thus indicating that quality control has not been implemented properly and improvements are needed to overcome these deviations. Thus H1 is proven correct, there are 6 types of damage that occur at PT Glory Industrial, namely looseness, broken fabric, embossed threads, skipped threads, damaged stitching and wrong labels. Based on the causes and effects, the factors that cause damage are human factors, machines, materials and work methods. Thus H2 is proven correct.